Arthron: uma ferramenta para gerenciamento e transmissão de mídia sem performances artístico-tecnológicas - Melo, Erick Augusto Gomes de (2010)
Developing and implementing a shared, distributed media spectacle requires some dedicated staff and a good plan so that errors can be minimized. Besides the technological necessary apparatus, it is imperative that everyone in the team be in complete synergy and artists have to worry about one more important point, not regarding to the artistic aspects, but regarding unavoidable technical aspects related to delays caused by network during transmission of live media streams. In this context of entanglement between Art and Technology that it was necessary to develop a tool that is able to support in a systematic way the performance of such shows. This software tool, named Arthron, offer to the user a simple interface for simultaneously manipulate different sources and pre-recorded or live media streams. Thus, the users can remotely add, remove, set the presentation format and adjust exhibition scheduling in time (when to present?) and space (where to present?) of media streams in a technological-artistic performance.